The Effects of Crystal Methamphetamine Consumption on Creatine Kinase Concentration and Oxidative Stress Markers in Human Subjects - Doaa Qasim Abbas; Mutashar Jaddoa Jiheel; Mahdi Abdul Karim (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study was designed to investigate the effect of crystal meth on the cardiovascular system. This research aims to study the relationship between methamphetamine consumption, creatine kinase levels, and oxidative stress indicators in a sample of individuals. By analyzing these factors, we can provide valuable insights into the health risks associated with this drug and develop effective treatment strategies for addicts. The study was designed to examine the effect of methamphetamine on heart system , with a focus on cardiovascular disease. The study included a group of 50 addicted participants and 40 control participants. Tests were performed to determine creatine kinase levels and oxidative stress indicators. Theresults showed a significant difference between addicts and healthy individuals. Creatine kinase levels in the addicted group were compared to the control group levels. The results also showed that the levels of total oxidants were higher in the control group compared to the addict group . The results indicate that methamphetamine consumption is associated with elevated creatine kinase levels, indicative of muscle tissue damage. Negative effects on the antioxidant system also promote oxidative stress, which increases the risk of chronic diseases.